Integrasi Nilai-Nilai Adat dan Budaya Lokal Tapanuli Selatan dalam Program Pembinaan Karakter Siswa di Madrasah - Hendra Irwandi Siregar; Syafnan Syafnan (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This paper aims to examine how the values of local customs and culture of South Tapanuli can be integrated in the character-building program of students in Madrasah. In the context of education, character is one of the important aspects that must be considered to form a generation that has good morality and a sense of love for the country. Along with the times, the process of preserving local culture is also increasingly threatened, so the integration of local culture in character education becomes very relevant. This paper uses a qualitative research method with a systematic literature review approach to identify cultural values that exist in South Tapanuli society, such as the concept of gotong royong, respect for parents, and the principles of simplicity and togetherness. These values are believed to be a strong foundation in the character-building process in Madrasahs, as well as instilling pride in the local culture itself. The results of this study indicate that the application of South Tapanuli customary and cultural values in character building in Madrasahs not only enriches the curriculum, but also strengthens social relations between students and between students and the surrounding environment.